(untitled) (African Journal of Biomedical Research, 2020)
With the dominance of its risk factors, non-alcoholic fatty liver disease (NAFLD) became common with high morbidity, nationally and worldwide. Early pathogenic implication of cellular hypoxia in asymptomatic simple non-alcoholic isolated hepatosteatosis (ANIHS) was investigated in this cross-sectional study and correlated changes in systemic hypoxia biomarkers with body mass index (BMI) in apparently healthy ANIHS participants with normal liver enzymes and size. We enrolled 180 adult consented volunteering Saudi participants in the period from January 1 to June 1, 2019. They comprised of normal lean healthy controls (n = 40; BMI = 18.5-25) and ANIHS participants (n 140) that were subdivided as overweight (n = 64; BMI = 25.1 – 30) and obese (n = 76; BMI >30 - <40). Male/female ratio was 1:1 and age range was 24 – 50 years (37.0 ± 7.85) without significant differences among groups. The cellular hypoxia biomarkers; lactate, pyruvate, lactate: pyruvate (L/P) ratio & hypoxia inducible factor (HIF)-1α were estimated in fasting plasma. Lactate was significantly higher in obese ANIHS compared to each of overweight ANSHS participants and controls. Pyruvate was significantly lowest in overweight ANIHS followed by obese ANIHS participants - compared to highest level in controls. L/P ratio was highest in obese ANIHS followed by overweight ANIHS participants, compared to controls. HIF-1α was more than 3-folds higher in obese ANIHS participants compared to healthy controls, with a mild increase in overweight ANIHS participants. Pyruvate and the ratio were significantly connected to steatosis, whereas lactate and HIF-1α were significantly connected to both BMI and hepatosteatosis. Cellular hypoxic changes may be implicated in pathogenesis of ANIHS. Plasma HIF-1α level reflects the correlation between BMI and occurrence/progression of ANIHS. Cellular hypoxia with responsive increases in HIF-1α could be prognostically good provided that it correlates a cytoprotective functional transcriptional response.